Active Zone Material-Directed Orientation, Docking, and Fusion of Dense Core Vesicles Alongside Synaptic Vesicles at Neuromuscular Junctions - Jung, Jae H.; Szule, Joseph A.; Stouder, Kylee; Marshall, Robert M.; McMahan, Uel J. (Frontiers in Neuroanatomy, 2018)
Active zone material is an organelle that is common to active zones along the presynaptic membrane of chemical synapses. Electron tomography on active zones at frog neuromuscular junctions has provided evidence that active zone material directs the docking of synaptic vesicles (SVs) on the presynaptic membrane at this synapse. Certain active zone material macromolecules connect to stereotypically arranged macromolecules in the membrane of undocked SVs, stably orienting a predetermined fusion domain of the vesicle membrane toward the presynaptic membrane while bringing and holding the two membranes together. Docking of the vesicles is required for the impulse-triggered vesicle membrane-presynaptic membrane fusion that releases the vesicles’ neurotransmitter into the synaptic cleft. As at other synapses, axon terminals at frog neuromuscular junctions contain, in addition to SVs, vesicles that are larger, are much less frequent and, when viewed by electron microscopy, have a distinctive electron dense core. Dense core vesicles at neuromuscular junctions are likely to contain peptides that are released into the synaptic cleft to regulate formation, maintenance and behavior of cellular apparatus essential for synaptic impulse transmission. We show by electron tomography on axon terminals of frog neuromuscular junctions fixed at rest and during repetitive impulse transmission that dense core vesicles selectively dock on and fuse with the presynaptic membrane alongside SVs at active zones, and that active zone material connects to the dense core vesicles undergoing these processes in the same way it connects to SVs. We conclude that undocked dense core vesicles have a predetermined fusion domain, as do undocked SVs, and that active zone material directs oriented docking and fusion of these different vesicle types at active zones of the presynaptic membrane by similar macromolecular interactions.